Public Space and Ideal City Concept: a Journey Between Renaissance and Modernism - Aksoy Oral, Emine Merve (My University, 2019)
In the Renaissance period, the first theoretical studies on urban planning and the search for order based on mathematical ratio, symmetry and human proportions are conducted. In addition to the physical space determined by geometric rules, a social arrangement takes place as a means of architecture. During this period, the Municipal Palaces, where public power is represented are located along with the religious buildings in idealized city squares. As the growing trade becomes the focal point of everyday life, the city squares are projected and designed in a trade-oriented way including market places. There are parallels between urban planning and designed public spaces in the Ancient Roman period and the point of view that revived the antiquity of the Renaissance period. In the 20th century, in the light of urban planning principles determined from a modernist point of view, "contemporary ideal city" projections are formed. Similar to the regulation of the physical space determined through rigid, geometric rules in the Renaissance period, idealized cities were projected and designed during the Modernist period. The study aims to investigate the concept of public space in urban planning and the visions of the "ideal city" during Renaissance and Modernist periods. Analyzing first the prominent city models and ideal squares in the historical process up to Modernist era, the research will examine the "ideal city" designs developed by Le Corbusier and set forth the old-new relations in search of creating the ideal order. In the study, the concept of ideal city during the Renaissance period will be explored both from theoretical and practical perspectives through both architectural treatises of Da Vinci, Alberti and Filarete with his ideal city "Sforzinda" and Pienza as a realized example. Le Corbusier's contemporary city plans and the modernist urban planning principles pointed out during CIAM meetings will be examined in reference to Renaissance regarding the same desire for social order. As a result, the similarities in the architectural approaches through periods will be laid out.
Keywords: Architectural Treatise; Ideal City; Ideal Square; Public Space; Order; Mimari İnceleme; İdeal Şehir; İdeal Kare; Kamusal Mekan